Features of some transcription factors gene expression in the malignancy tissues of the corpus uteri - D. S. Kutilin; I. S. Nikitin; O. I. Kit (Успехи молекулярной онкологии, 2019)
Background. Worldwide, more than 300,000 women are diagnosed with uterine cancer each year. Currently, the problem of finding highly specific molecular tumor markers for this disease remains relevant. Screening for gene expression of transcription factors responsible for controlling the differentiation of cells of endometrial tissues may allow the formation of a tumor markers panel and explore the fundamental mechanisms of oncotransformation.Objective of our study was to analyze changes in the expression of transcription factors OCT4, SOX2 and C-MYC in the tissues of the uterus (corpus uteri) during the process of their malignancy.Materials  and methods. Uterus tissue biopsy specimens of 45 patients (tumor and non-tumor) were used for the study. To determine the relative expression of 3 genetic loci encoding the transcription factors OCT4, SOX2 and C-MYC the real-time polymerase chain reaction method, ACTB was used as the reference gene.Results. A change of OCT4, SOX2 and C-MYC genes transcriptional activity in uterus tumor cells is found as the tumor develops. By reducing the tumor cells differentiation degree expression of OCT4 gene increases most significantly, that confirmsits status of undifferentiated cellsmarker. As the differentiation degree of tumor cells decreases, OCT4, SOX2 and C-MYC genes expression change affects the adjacent conditionally normal tissue of the uterus, but with less intensity, especially in the later stages of malignancy.Conclusion. The obtained data makes it possible to use the OCT4, SOX2 and C-MYC genes as differential markers of the tumor process development, and the SOX2 gene expression as a predictive marker of malignancy.